PESONA EKOWISATA MAGROVE DAN PEMANFAATAN HUTAN BAKAU DIKAMPUNG TUA SERIP BATAM - Pranoto, Suryo Budi (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2024)
The potential of the mangrove forest ecosystem to become a prominent ecotourism attraction that raises community awareness and fosters a love for mangrove conservation is still underdeveloped. Situated in the Old Mangrove Village of Serip, Nongsa District, Sambau Village, this coastal area boasts significant tourism potential, particularly in its beaches and mangrove ecosystems. Transforming mangrove forests into ecotourism sites aligns with the growing trend of tourists shifting from conventional tourism to more sustainable, nature-oriented experiences. This study uses SWOT analysis to formulate a development strategy for mangrove forest ecotourism. Strengths are the internal advantages an organization holds, such as skills, products, and resources, which aid in achieving its objectives. Weaknesses refer to internal limitations, including resource constraints and skill gaps, that hinder optimal performance. Opportunities are favorable external conditions that can be leveraged for growth, while threats are external factors that could pose challenges. Internal and external factors play a crucial role in the sustainability of mangrove forests and the development of mangrove ecotourism. The analysis reveals that there are more strengths and opportunities than weaknesses and threats. This suggests that there is significant potential to harness these strengths, particularly in the Kampung Tua Bakau Serip area, to develop ecotourism that not only preserves the environment but also creates new employment opportunities, especially within the local community. This can be achieved by enhancing existing attractions, adding complementary features, empowering residents, and transforming the area into a thriving hub for tourism.